Neuroprotective effects of curcumin-loaded emulsomes in a laser axotomy-induced CNS injury model - Yılmaz, Elif Nur; Bay, Sadık; Öztürk, Gürkan; Uçışık, Mehmet Hikmet (Dove Medical Press Ltd, 2020)
Purpose: Curcumin, a polyphenol isolated from the rhizomes of turmeric, holds great potential as a neuroprotective agent in addition to its anti-inflammatory and antioxidant characteristics. The poor bioavailability and low stability of curcumin are the greatest barriers to its clinical use. This study aims to investigate the neuroprotective effect of curcumin on axonal injury, by delivering the lipophilic polyphenol to a primary hippocampal neuron culture by means of a lipid-based drug delivery system, named emulsomes.Methods: To study neuroregeneration ex vivo, an injury model was established through single-cell laser axotomy on hippocampal neurites. Upon treatment with curcumin-loaded emulsomes (CurcuEmulsomes), curcumin and CurcuEmulsome uptake into neurons was verified by three-dimensional Z-stack images acquired with confocal microscopy. Neuron survival after axonal injury was tracked by propidium iodide (PI) and Hoechst staining. Alterations in expression levels of physiological markers, such as anti-apoptotic marker Bcl2, apoptotic marker cleaved caspase 3, neuroprotective marker Wnt3a and the neuronal survival marker mTOR, were investigated by immunocytochemistry analyses.Results: The results indicated significant improvement in the survival rate of injured neurons upon CurcuEmulsome treatment. Bcl2 expression was significantly higher for injured neurons treated with curcumin or CurcuEmulsome. Reduction in caspase 3 expression was seen in both curcumin and CurcuEmulsome treatment, whereas there were no significant changes in Wnt3a and mTOR expression.Conclusion: The established laser-axotomy model was proven as a reliable methodology to study neurodegenerative models ex vivo. CurcuEmulsomes delivered curcumin to primary hippocampal neurons successfully. Treated with CurcuEmulsomes, injured hippocampal neurons benefit from the neuroprotective effects of curcumin, exhibiting a higher survival rate and increased anti-apoptotic marker levels.
Keywords: Curcumin; Lipid-Based Nanodrug Delivery; Neurodegeneration; Hippocampus; Axon Injury